2017
DOI: 10.1186/s13068-017-0920-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Engineering Bacillus licheniformis as a thermophilic platform for the production of l-lactic acid from lignocellulose-derived sugars

Abstract: Background Bacillus licheniformis MW3 as a GRAS and thermophilic strain is a promising microorganism for chemical and biofuel production. However, its capacity to co-utilize glucose and xylose, the major sugars found in lignocellulosic biomass, is severely impaired by glucose-mediated carbon catabolite repression (CCR). In this study, a “dual-channel” process was implemented to engineer strain MW3 for simultaneous utilization of glucose and xylose, using l-lactic acid as a target product.ResultsA non-phosphotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…The RT‐qPCR results showed that genes involved in the xylose degradation pathway were both significantly upregulated in engineered SY‐ldh‐△ xylR , in which the relative transcription levels of xylA and xylB were upregulated by 65‐fold and 27‐fold respectively (Figure 6B ). Nevertheless, it was found that the average xylose consumption rate of SY‐ldh‐△ xylR was 0.338 ± 0.027 g/L/h, which was almost the same as that of SY‐ldh (0.335 ± 0.011 g/L/h) at 11 h (Figure 6C ), which was also reported in B. licheniformis (Li et al, 2017 ) and Clostridium cellulovorans (Wen et al, 2020 ). Therefore, we speculate that the low consumption rate of xylose was probably due to low efficiency of xylose transporters in SY‐ldh‐△ xylR .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The RT‐qPCR results showed that genes involved in the xylose degradation pathway were both significantly upregulated in engineered SY‐ldh‐△ xylR , in which the relative transcription levels of xylA and xylB were upregulated by 65‐fold and 27‐fold respectively (Figure 6B ). Nevertheless, it was found that the average xylose consumption rate of SY‐ldh‐△ xylR was 0.338 ± 0.027 g/L/h, which was almost the same as that of SY‐ldh (0.335 ± 0.011 g/L/h) at 11 h (Figure 6C ), which was also reported in B. licheniformis (Li et al, 2017 ) and Clostridium cellulovorans (Wen et al, 2020 ). Therefore, we speculate that the low consumption rate of xylose was probably due to low efficiency of xylose transporters in SY‐ldh‐△ xylR .…”
Section: Resultssupporting
confidence: 75%
“…It has been reported that the xylose metabolism negative regulator XylR could specifically repress the gene expression of the xylose pathway in some Gram‐positive organisms (Figure 6A ) (Li et al, 2017 ; Wen et al, 2020 ). To enhance xylose utilization in strain SY‐ldh, xylR was knocked out via CRISPR/Cas9.…”
Section: Resultsmentioning
confidence: 90%
“…The authors are retracting this article because the biological materials were used and the experiments were conducted without proper authorization from the laboratory where these data were obtained [ 1 ].…”
Section: Retraction To: Biotechnol Biofuels (2017) 10:235 101186/s13mentioning
confidence: 99%
“…However, these strains cannot utilize lignocellulosic biomass efficiently ( Abedi and Hashemi, 2020 ; Augustiniene et al, 2022 ). Although various metabolic engineering strategies have been applied to produce lactate efficiently from lignocellulosic biomass, such as enhancing the expression or activity of enzymes of lactate biosynthesis pathway, disrupting pathways that compete for carbon substrate, electrons and co-factors, as well as enhancing strain acid-stress tolerance by overexpressing the transporter related genes ( Li et al, 2017 ; Weusthuis et al, 2017 ; Zhang et al, 2017 ; Kong et al, 2019 ; Tsuge et al, 2019 ; Zhu et al, 2019 ), the large-scale industrial production of lactate from cost-effective feedstocks has not yet been commercialized.…”
Section: Introductionmentioning
confidence: 99%